2013
DOI: 10.1111/1744-9987.12070
|View full text |Cite
|
Sign up to set email alerts
|

Method for Approximating Colloid Osmotic Pressure in Long‐Term Hemodialysis Patients

Abstract: Colloid osmotic pressure (COP) is important in calculating vascular permeability during hemodialysis (HD). However, few reports have directly measured COP in HD patients. Therefore, the currently published formulas may not be clinically optimal for predicting COP for HD patients. Here, the study aims were (i) to directly measure COP in HD patients and compare the measured and predicted COP values using four previously reported formulas, and (ii) to develop a formula for approximating COP using clinical paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…Regarding the association between cerebral rSO 2 and nutritional parameters in this study, serum albumin concentration and Hb level were significantly associated with cerebral rSO 2 in multivariate linear regression analysis. Serum albumin concentration, the main determinant of colloid osmotic pressure in vessels, plays an important role in maintaining microcirculation in systemic tissues via the movement of body fluids, mainly between the vessels and interstitium [43]. Furthermore, consistent with the present study, serum albumin concentration has been reported to be significantly associated with cerebral oxygenation in patients with all stages of CKD, as well as patients undergoing HD [15,17].…”
Section: Discussionsupporting
confidence: 83%
“…Regarding the association between cerebral rSO 2 and nutritional parameters in this study, serum albumin concentration and Hb level were significantly associated with cerebral rSO 2 in multivariate linear regression analysis. Serum albumin concentration, the main determinant of colloid osmotic pressure in vessels, plays an important role in maintaining microcirculation in systemic tissues via the movement of body fluids, mainly between the vessels and interstitium [43]. Furthermore, consistent with the present study, serum albumin concentration has been reported to be significantly associated with cerebral oxygenation in patients with all stages of CKD, as well as patients undergoing HD [15,17].…”
Section: Discussionsupporting
confidence: 83%
“…Serum albumin concentration, the main determinant of colloid osmotic pressure in vessels, plays an important role in the regulation of fluid exchange across the microvascular wall. Therefore, albumin itself plays an essential role in maintaining microcirculation in systemic tissues via the body- fluid movement, mainly between the vessels and interstitium [ 29 ]. To date, serum albumin concentration has reportedly been associated with CKD progression [ 30 ], prognosis in CKD patients [ 31 ], and trajectory of cognitive function in community-dwelling adults [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cerebral oxygen supply decrease induced by severe anemia, the significant decrease in serum albumin concentration in HD patients with severe anemia might be associated with the cerebral rSO 2 reduction in this study. Colloid osmotic pressure is one of the important factors maintaining a systemic microcirculation (including that in the brain), and serum albumin concentration mainly constitutes the formation of colloid osmotic pressure [19]. In HD patients with well-maintained Hb levels, cerebral rSO 2 was independently and positively associated with serum albumin concentration [6].…”
Section: Discussionmentioning
confidence: 99%